The Effect of Informal and Formal Networking on Uncertainty and the Performance in the German Automotive Industry - Kreiser, Johanna; Srivastava, Mohit; Tyll, Ladislav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
Organizations all over the world interact within networks. Such network formations are mostly driven by the need to access resources or to reduce uncertainties and problem within the organization or in its business environment. This paper investigates, how informal and formal network behaviours moderate such uncertainties and thereby, increase the perfor-mance. This study is conducted to close the gap of missing industry-focused research in this field of study. Data were derived from a questionnaire, explicitly focused on the German automotive market. The results show that formal networking does not moderate or reduce the effect of informal and formal uncertainties, whereas informal networking does moderate or mitigate the effect of informal uncertainties and thereby, increases the organization’s perfor-mance. As an additional finding of this paper, the results suggest, that informal networking increase the negative effect of formal uncertainties. These findings indicate that networking should be tailored per the types of uncertainty to have a positive effect on performance.
Vedoucí práce: Mohit Srivastava
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses